The real motivations that fresh students had in tha choice of the career of Licenciatura en Idioma Inglés, opción enseñanza, of the foreign languages Departament of the University of El Salvador, semester I - 2003 - Perla Fuentes, Yeni Carolina; Delgado Martínez, Glenda de los Angeles; Salazar Murcia, Pedro Antonio (San Salvador : Universidad de El Salvador, 2003)
Some years up to now it has been heard that many of the fresh students that decide to study the career of Licenciatura en Idioma Inglés, opción Enseñanza in the University of El Salvador have not been motivated to study this career with the purpose to become teachers. Most of the fresh students that entered to this career in the semester I year 2003 have not been the exception, since they have expressed they do not want to perform as teachers and instead of that they have other motivations. Of course, not all of them have the same goals to study this career, this means that there are a few of them that are motivated to study this major with the purpose to become teachers that is the purpose of this career. But, why the other students do not have the motivation to become teachers? Most fresh students’ objective is not teaching English but getting better opportunities to get jobs, travelling to other countries, working as translators , interpreters, working in airlines, and studying English since it was their favourite subject in high school.
Incluye glosario
Tesis (Licenciatura en Idioma Inglés opción enseñanza) -- Universidad de El Salvador
Bibliografía : h. 25-26
Keywords: Inglés -- Enseñanza; Intereses vocacionales